Sistem Kendali Pencahayaan Lampu Penerangan Jalan Untuk Menghemat Energi Listrik - Winarso; Latiful Hayat (UM Purwokerto Press, 2026)
The progress of a city can be seen in its lighting system, such as billboard lights, street lights and traffic control systems. Lighting the lights on each street requires a lot of electrical energy because there are quite a number of these lights and they light up for a long time. The street lighting system will beautify buildings, shops, hotels and offices at night and create a sense of security for the community. The purpose of this study is to utilize a street light lighting control system to adjust the intensity of street lighting according to busy road conditions. This research method was carried out by observing the amount of energy used by conventional street lights and observing the energy absorbed by street lights with controls according to the needs of street lighting intensity. In this study, the energy entering the lamp is regulated from 18.00 - 22.00 by 100%, at 22.01 - 24.00 by 55%, at 00.01 - 04.00 by 30% and at 04.01 - 05.59 by 100% so that it can save energy by 42, 55% compared to 50 watt COB lamps which are supplied 100% from 18.00 - 05.59. Energy savings of 42.55% if implemented within one month can save around 9.66 kwh and if implemented within one year can save 115.92 kw